2017
DOI: 10.15644/asc51/4/6
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Nickel-Titanium Orthodontic Archwires in Saliva and Oral Probiotic Supplements

Abstract: ObjectivesThe aim of the study was to examine how probiotic supplements affect the corrosion stability of orthodontic archwires made of nickel-titanium alloy (NiTi).Materials and MethodsNiTi archwires (0.508x0.508 and having the length of 2.5 cm) were tested. The archwires (composition Ni=50.4%, Ti=49.6%) were uncoated, nitrified and rhodium coated. Surface microgeometry was observed by using scanning electron microscope and surface roughness was measured by profilometer through these variables: roughness aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This element is an essential nutrient involved in morphological functions, growth, and development, including germination, and is naturally present in plant organs. It is frequently associated with primitive systems, such as those in anaerobic bacteria [ 26 ]. Although it is not essential for humans, Ni has been studied for its potentially harmful effects on health [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…This element is an essential nutrient involved in morphological functions, growth, and development, including germination, and is naturally present in plant organs. It is frequently associated with primitive systems, such as those in anaerobic bacteria [ 26 ]. Although it is not essential for humans, Ni has been studied for its potentially harmful effects on health [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research imply that probiotic supplement affects corrosion resistance and that the occurrence of general and localized corrosion is influenced by the type of coating of NiTi alloy [26]. It seems to influence general corrosion of rhodiumcoated alloy and causes localised corrosion of uncoated and rhodium-coated alloy.…”
Section: Roughnessmentioning
confidence: 93%
“…Low hydrofluoric acid concentration decreases corrosion resistance while high concentration improves it [29]. It was previously reported that probiotic supplement does not change roughness of NiTi alloys compared to the effect of saliva alone [26], but the profilometer analysis method is inferior to the atomic force microscopy method used here [31].…”
Section: Roughnessmentioning
confidence: 96%
“…Corrosion of orthodontic archwires can occur due to saliva (composed of inorganic salts, organic and gastric acids) and/or biofilm properties (community of microorganisms attached to the surface of teeth and archwires) [ 94 ]. Studies analysed the effect of probiotics on corrosion of different types of archwires and orthodontic materials: nickel-titanium (NiTi) alloys (uncoated, nitrified and rhodium coated surface) [ 94 , 95 ], titanium and stainless steel (SS) [ 94 , 96 ]. A mixture of artificial saliva with dissolved L. reuteri Prodentis® DSM 17938 and ATCC PTA 5289 (BioGaia, BioGaia AB, Sweden) was shown to have less corrosive effects on an uncoated surface (BioForce Sentalloy®, Dentsply International GAC, United States), comparable effects on nitrified surfaces and higher local and general corrosive side effects on rhodium coated surfaces compared to artificial saliva alone, indicating that surface roughness induced by probiotic was not greater than induced by saliva [ 95 ].…”
Section: Methodsmentioning
confidence: 99%